The Puerto Rico Alzheimer Disease Initiative (PRADI): A Multisource Ascertainment Approach - Feliciano-Astacio, Briseida E.; Celis, Katrina; Ramos, Jairo; Rajabli, Farid; Adams, Larry Deon; Rodriguez, Alejandra; Rodriguez, Vanessa; Bussies, Parker L.; Sierra, Carolina; Manrique, Patricia; Mena, Pedro R.; Grana, Antonella; et al. (Frontiers in Genetics, 2019)
Introduction: Puerto Ricans, the second largest Latino group in the continental US, are underrepresented in genomic studies of Alzheimer Disease (AD. To increase representation of this group in genomic studies of AD, we developed a multisource ascertainment approach to enroll AD patients and their family members living in Puerto Rico (PR) as part of the Alzheimer’s Disease Sequencing Project (ADSP), an international effort to advance broader personalized/precision medicine initiatives for AD across all populations. Methods: The Puerto Rico Alzheimer Disease Initiative (PRADI) multisource ascertainment approach was developed to recruit and enroll Puerto Rican adults aged 50 years and older for a genetic research study of AD, including individuals with cognitive decline (AD, mild cognitive impairment), their similarly aged family members, and cognitively healthy unrelated individuals age 50 and up. Emphasizing identification and relationship building with key stakeholders, we conducted ascertainment across the island. In addition to reporting on PRADI ascertainment, we detail admixture analysis for our cohort by region, group differences in age of onset, cognitive level by region, and ascertainment source. Results: We report on 674 individuals who met standard eligibility criteria (282 AD-affected participants [42% of the sample], 115 individuals with mild cognitive impairment (MCI) [17% of the sample], and 277 cognitively healthy individuals [41% of the sample]). There are 43 possible multiplex families (10 families with 4 or more AD-affected members and 3 families with 3 AD-affected members). Most individuals in our cohort were ascertained from the Metro, Bayaman, and Cauguas health regions. Across health regions, we found differences in ancestral backgrounds and select clinical traits. Discussion: The multisource ascertainment approach used in the PRADI study highlights the importance of enlisting a broad range of community resources and providers. Preliminary results provide important information about our cohort that will be useful as we move forward with ascertainment. We expect that results from the PRADI study will lead to a better understanding of genetic risk for AD among this population.